Narrowing Vertical Fiscal Imbalances in Four European Countries - Karpowicz, Izabela (IMF Working Papers; Working Paper ;, 2012)
This paper describes the institutional changes that have induced a decline in the vertical fiscal imbalance (VFI) - defined as the share of sub-national own spending not financed through own revenues - in four European countries: Belgium, Italy, Norway, and Spain. The decline in VFI was achieved through progressive devolution of revenues to sub-national governments in Belgium, Italy, and Spain, while re-centralization of health sector expenditures was the cause of the decline in the VFI in Norway.